An experimental investigation of water level effects on the dynamic behaviour of a large arch dam. - Proulx, Jean (Earthquake engineering & structural dynamics.)
The need for full scale dynamic tests, which are recognized as the most reliable method to evaluate a structure's vibration properties, is increasing as new analysis techniques are developed that take into account the complex interaction phenomenons that occur in dam reservoir foundation systems. They are extremely useful to obtain reliable data for the calibration of newly developed numerical methods. The Earthquake Engineering and Structural Dynamics Research Center (CRGP) at the University of Sherbrooke has been developing and applying dynamic testing methods for large structures in the past 10 years. This paper presents the experimental evaluation of the effects of the varying water level on the dynamic response of the 180 m Emosson arch dam in Switzerland. Repeated forced vibration tests were carried out on the dam during four different periods of the reservoir's filling cycle during a one year span. Acceleration and hydrodynamic pressure frequency responses were obtained at several locations while the dam was subjected to horizontal harmonic loading. The variation of the resonant frequencies as a function of the reservoir level is investigated. A summary of the ongoing numerical correlation phase with a three dimensional finite element model for the dam reservoir foundation system is also presented.